Diminishing clear winter skies in Beijing towards a possible future. (18th December 2018) - Pei, Lin; Yan, Zhongwei
Abstract: Severe haze during the winter season has been troubling the citizens of Beijing over the past few decades, and the trend seems to be continuing. However, occasionally such as the winter of 2017 (2017/12–2018/2), one would be amazed to see unusually few hazy days throughout the winter that brings memories of a long past. It is controversial to say whether such a nowadays-rare event is a result of policy-driven emission cuts or an opportunity brought about by natural climate variability. This paper investigates the probability of such anomalous atmospheric circulation events in winter from a climate perspective. Based on updated observations, only three winters during the past 38 years are found to be similar to that of 2017. These events were accompanied by a strong Siberian High to the north and cold anomalies in the mid-lower troposphere in association with a strong East Asian Trough, which favored the strengthening of northwesterly winds and effective ventilation. The occurrences of such favorable winter circulation anomalies are found to have decreased by about 50% from the 1st to the 2nd half of the 20th century. A further 60% [11.4%, 89.3%] reduction between 1951–2000 and 2050–2099 is projected by climate models under the IPCC's Representative Concentration Pathway 8.5 scenario. Without serious cuts in pollution emissions, winters are projected to be dismal for the 20 million people of Beijing to a possible future under global warming.